Synthesis, structure, and properties of the high-temperature superconductor HgBa2CuO4+delta - Hodges, J; Gameson, I; Edwards, P; Kharel, A; Porch, A (1997)
We report here the attempted synthesis of (Hg1-xCuy)Ba2CuO4+δ (0≤x≤0.2, 0≤y≤0.2, y≤x) and the results of a detailed characterization of the structural and superconducting properties of the resulting samples. Rietveld refinement of powder x-ray-diffraction data collected on all 15 samples synthesized found no partial Cu occupancy of the Hg site. We therefore conclude that for these samples no solid solution exists and the superconducting phase is simply HgBa2CuO4+δ. Only one interstitial oxygen position O(3) was found, located exactly at the center of the Hg plane. An analysis of the structural refinements has produced a number of correlations between the exact location of the Ba2+ cation within the unit cell and a number of important superconducting parameters; these include the occupancy of the O(3) site, the extent of oxidation of the CuO2 planes, and the magnetic penetration depth.